A suitable method for alpine wetland delineation: An example for the headwater area of the yellow river, Tibetan Plateau - Yin, Tao; Feng, Yuqing; Liang, Sihai; Wang, Guangjun; Yuan, Ning; Yan, Dezhao; Wu, Pan; Kuang, Xingxing; Wan, Li (Frontiers in Environmental Science, 2022)
Wetlands are among the world's most important ecosystems because of their rich biological environments and their critical role in regulating the hydrological cycle. Alpine wetlands have been damaged to varied degrees as a result of climate change and have become study hotspots. However, alpine wetlands studies are hindered by the unreliability of existing wetland data. The boundary between wetland and alpine meadow was blurred, and the flood wetland was not identified. This study used an object-oriented and decision tree classification model (ODTC) based on geomorphological types applied to Landsat 8 data and a new wetland classification system to build the wetland map of the Headwater Area of the Yellow River (HAYR), China. The overall classification accuracy rate was 98.9%. The wetland extraction obtained in this study was compared to seven commonly used extraction methods and outperformed them by 10%-20%. According to our result, the HAYR's wetland area is 3,142.3km2, accounting for 16.1% of the study region’s total area. The marsh comprised most of the wetland area, accounting for 37.7%, while the flood wetland areas are the least extensive, accounting for 16.7%. A three-dimensional map of the area showed that alpine wetlands in the research region are distributed around lakes, piedmont groundwater overflow belts, and inter-mountain catchment basin. This phenomenon demonstrates that hydrogeological circumstances influence alpine wetlands’ genesis and evolution. This work provides a new approach to investigating alpine wetlands.